Preparation and Characterization of Graphene Oxide Aerogels: Exploring the Limits of Supercritical CO2 Fabrication Methods. Issue 59 (2nd October 2018) - Borrás, Alejandro; Gonçalves, Gil; Marbán, Gregorio; Sandoval, Stefania; Pinto, Susana; Marques, Paula A. A. P.; Fraile, Julio; Tobias, Gerard; López‐Periago, Ana M.; Domingo, Concepción
Abstract: The supercritical carbon dioxide (scCO2 ) synthesis of non‐reduced graphene oxide (GO) aerogels from dispersions of GO in ethanol is here reported as a low‐cost, efficient, and environmentally friendly process. The preparation is carried out under the mild conditions of 333 K and 20 MPa. The high aspect ratio of the used GO sheets (ca. 30 μm lateral dimensions) allowed the preparation of aerogel monoliths by simultaneous scCO2 gelation and drying. Solid‐state characterization results indicate that a thermally‐stable mesoporous non‐reduced GO aerogel was obtained by using the supercritical procedure, keeping most of the surface oxygenated groups on the GO sheets, thus, facilitating further functionalization. Moreover, the monoliths have a very low density, high specific surface area, and excellent mechanical integrity; characteristics which rival those of most light‐weight reduced graphene aerogels reported in the literature. Abstract : Critical condition : The supercritical carbon dioxide synthesis of non‐reduced graphene oxide (GO) aerogels from dispersions of GO in ethanol is here reported as a low‐cost, efficient, and environmentally friendly process. Moreover, the monoliths have a very low density, high specific surface area, and excellent mechanical integrity; characteristics which rival those of most light‐weight reduced graphene aerogels reported in the literature.